Gambaran GAMBARAN FAKTOR PENYEBAB PERSALINAN SECTIO CAESAREA DI RUMAH SAKIT TK IV DKT KOTA KEDIRI - Antika, Antika Agus; Dwi Antono, Sumy; Pratamaninngtyas, Susanti; Sendra, Eny (Universitas Kadiri, 2024)
Caesarean section is the separation of the abdominal wall and uterus when the uterus and intact fetus weigh at least 500 grams. Nowadays, more and more mothers are giving birth via SC due to several factors. Although the risk of caesarean delivery is higher than vaginal delivery, this type of delivery has become a trend among the general public. This number is expected to continue to increase in the coming years, with almost (29%) more births by 2030. This study aims to determine the causes of SC delivery in TK IV DKT Hospital, Kediri City. The type of research used is descriptive, which describes the phenomenon in its actual state, not a manipulative process, which describes the situation in its current form. Total sampling technique was used in this study to obtain a sample size of 327 people. Equipment or measuring instruments used included the collection of patient medical record data and the use of observation record sheets and analyzed univariate. The results showed that the most common causative factors of SC in TK IV DKT Hospital in Kediri City were maternal factors, PROM by 28.75% and breech factors by 4.89%.